Optimization of Pretreatment and Hydrolysis Steps and Estimation of Theoretical Bioethanol Potential from Cattle Manure - Samomssa Inna; Oumarou Amadou Amadou; Djou Brice; Kamga Richard (Sustainable Chemical Engineering, 2024)
The depletion of fossil fuels, the pollutant related issues,insecure supply chains of biomass, and the increasing energy prices leads to finding alternative energy sources. The goal of this study was to optimize bioethanol production from cattle manure and to estimate the theoretical bioethanol potential. To achieve this goal, both acid/and alkaline pretreatments and hydrolysis steps were optimized using H2SO4 and NaOH. A centered central composite design was used for acid pretreatment optimization, and a central composite design was applied for alkaline pretreatment and diluted acid hydrolysis with respect to physico-chemical parameters. The existing kinetic models were used to estimate bioethanol potential and to follow the degradation of macromolecules to bioethanol. The alkaline pretreatment offered 35% as the highest cellulose content for the time of 5 h and the NaOH concentration ranged between 2 M to 2.3 M. Meanwhile, the highest phenolic compound content was 800 mg/100 g for time varying between 3.7 h and 5 h and NaOH concentration ranged from 1.3 M to 2 M. The acid pretreatment revealed that the optimum area reached 45.5% sugar-free for acid concentration between 3.5 M and 4 M and time ranged from 9 min to 10 min. The results from acid hydrolysis pointed out that the maximum value of sugar-free was 78% for time ranging from 1.9 h to 2 h and the sulfuric acid concentration between 2.9 M and 3.0 M. The amount of cellulose per year was estimated at 593,271 t/year and the amount of bioethanol potential was evaluated at 461,433,000 L/year. The kinetic hydrolysis model based on sulfuric acid concentration showed that the maximum time of hydrolysis and the cellulose decreased when the temperature increased while the quantity of glucose followed the evolution of the temperature. Hence, temperature plays a very important role during the hydrolysis of cellulose. The satisfactory results obtained from this work display that, the production of bioethanol from cattle manure could permit improved environmental sustainability.